EFFECTIVENESS OF “PROGRAM DESA MANDIRI PANGAN (DMP)” IN SUPPORTING AGRICULTURAL PRODUCTION AND HOUSEHOLD FOOD SECURITY IN WONOSOBO DISTRICT - Himawan Wahyu Pamungkas; Anang M. Legowo; Mukson Mukson (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Wonosobo Regency is the district with the highest poverty rate in Central Java, reaching 17.58% in 2018. Based on the FSVA map, there are nine sub-districts in Wonosobo Regency with food security criteria (priority 5). The Food Independent Village Program is one of the critical interventions in poverty alleviation and increasing food security. The aims of this research are: 1) to describe socialization and training, mentoring, institutional growth, member participation, the commitment of policymakers, agricultural production, and household food security in Wonosobo Regency; 2) to analyze the influence between socialization and training, mentoring, institutional growth. The research was conducted using a quantitative approach with a survey method. The research location was determined based on consideration of the high poverty level, the condition of food security and vulnerability, and the location of the DMP program village. Sampling was carried out on 118 household heads receiving the DMP program in Reco Village and Kapencar Village. Data was collected based on interviews using questionnaires and observations. The Linkert scale measures variables using: strongly disagree, disagree, undecided, agree, and strongly agree. Descriptive analysis was used to examine respondents' responses to the variables of socialization and training, mentoring, institutional growth, member participation, the commitment of policymakers, agricultural production, and household food security. Based on descriptive analysis, respondents gave responses with high categories for the variables of training socialization, mentoring, institutional growth, member participation, and commitment of policymakers, agricultural production, and household food security. The inner study of the SEM analysis model of the PLS method stated that the variables of socialization and training, mentoring, institutional growth, member participation, and commitment of policymakers had a significant effect on agricultural production. Furthermore, socialization, training, and institutional development significantly impact food security. Still, the variable of assistance, member participation, and policymakers' commitment does not significantly affect food security.